Association of plant-based diet index with prostate cancer risk. Issue 3 (13th November 2021) - Loeb, Stacy; Fu, Benjamin C; Bauer, Scott R; Pernar, Claire H; Chan, June M; Van Blarigan, Erin L; Giovannucci, Edward L; Kenfield, Stacey A; Mucci, Lorelei A
ABSTRACT: Background: Plant-based diets are associated with multiple health benefits and a favorable environmental impact. For prostate cancer, previous studies suggest a beneficial role of specific plant-based foods (e.g., tomatoes) and a potentially harmful role of specific animal-based foods (e.g., meat, dairy). However, less is known about plant-based dietary patterns. Objectives: We sought to examine the relation between plant-based diet indices and prostate cancer risk, including clinically relevant disease. Methods: This was a prospective cohort study including 47, 239 men in the Health Professionals Follow-Up Study (1986–2014). Overall and healthful plant-based diet indices were calculated from FFQs. Cox proportional hazards models were used to estimate HRs and 95% CIs to examine the risk of incident prostate cancer (total and by clinical category), among men ages <65 and ≥65 y. Results: Of the 47, 239 men, 6655 men were diagnosed with prostate cancer over follow-up, including 515 with advanced-stage disease at diagnosis, 956 with lethal disease (metastasis or death), and 806 prostate cancer deaths. Greater overall plant-based consumption was associated with a significantly lower risk of fatal prostate cancer (HR: 0.81; 95% CI: 0.64, 1.01; P -trend = 0.04). In men aged <65, a higher plant-based diet index was associated with a lower risk of advanced, lethal, and fatal prostate cancer. Moreover, greater consumption of a healthful plant-based diet was associated with lower risks of total (HR: 0.84; 95% CI: 0.73, 0.98; P -trend = 0.046) and lethal prostate cancer (HR: 0.56; 95% CI: 0.34, 0.94; P -trend = 0.03) at age <65. There were no associations between overall or healthful plant-based diet indices with prostate cancer among men ≥65 y. Fewer than 1% of participants followed a strict vegetarian or vegan diet. Conclusions: This prospective study provides supportive evidence that greater consumption of healthful plant-based foods is associated with a lower risk of aggressive forms of prostate cancer, with stronger benefit among men aged <65 y.